Auditory listening effort and reaction time: a comparative study between single sided deaf cochlear implant users and normal hearing controls - Voola, Marcus Windsor Rao; Tavora-Vieira, Dayse; Wedekind, Andre; Bogdanov, Caris; Acharya, Aanand (Frontiers in Audiology and Otology, 2024)
Introduction Cochlear implant (CI) provision has been shown to be the only hearing rehabilitation option that can improve speech perception in noise and sound localization in SSD listeners. Individuals with SSD are known to exert increased listening effort when compared to normal hearing individuals, and this remains true even with CI use. Recently, reaction time (RT) has emerged as a promising metric for quantifying listening effort. As such, the current study compared performance (RT and Accuracy) of SSD participants (with and without the use of their CI) to normal hearing (NH) listeners. We assessed three listening conditions: (1) monaural listening in quiet, (2) free field listening in quiet, and (3) free field listening in background noise. Method SSD CI data was retrospectively obtained from two past studies conducted by the group. For monaural listening and free field listening in quiet, the same 10 SSD CI participants and 10 NH controls was recruited. For free field listening in noise condition, 12 SSD CI participants and 12 NH controls were recruited. In all condition, participants were required to complete an auditory oddball task, discerning odd and even numbers. RT and target accuracy were the metrics recorded. Results In monaural listening conditions, SSD CI users exhibited significantly delayed RTs compared to their NHE and to NH controls when stimuli was played directly through the CI. Surprisingly, the RT for the NHE of SSD CI users was also delayed when compared to the NH controls. Free field listening in quiet conditions showed increased RTs for SSD CI users, with and without CI, compared to NH controls, indicating the persistent impact of SSD on processing. In free field listening in noise, CI use significantly improved RTs for SSD individuals but did not reach NH levels. Despite the RT differences, task accuracy remained comparable between groups. Discussion SSD CI users exhibited longer RTs in all test conditions, suggesting they expend more listening effort than normal hearing controls. This increased effort likely accounts for the delayed RTs, highlighting the additional processing challenges faced by SSD CI users.